Decreased GLUT1/NHE1 RNA expression in whole blood predicts disease severity in patients with COVID‐19. (20th November 2020) - Mustroph, Julian; Hupf, Julian; Hanses, Frank; Evert, Katja; Baier, Maria J.; Evert, Matthias; Meindl, Christine; Wagner, Stefan; Hubauer, Ute; Pietrzyk, Gabriela; Leininger, Simon; Staudner, Stephan; et al.
Abstract: Aims: We aimed to assess whether expression of whole‐blood RNA of sodium proton exchanger 1 (NHE1) and glucose transporter 1 (GLUT1) is associated with COVID‐19 infection and outcome in patients presenting to the emergency department with respiratory infections. Furthermore, we investigated NHE1 and GLUT1 expression in the myocardium of deceased COVID‐19 patients. Methods and results: Whole‐blood quantitative assessment of NHE1 and GLUT1 RNA was performed using quantitative PCR in patients with respiratory infection upon first contact in the emergency department and subsequently stratified by SARS‐CoV‐2 infection status. Assessment of NHE1 and GLUT1 RNA using PCR was also performed in left ventricular myocardium of deceased COVID‐19 patients. NHE1 expression is up‐regulated in whole blood of patients with COVID‐19 compared with other respiratory infections at first medical contact in the emergency department (control: 0.0021 ± 0.0002, COVID‐19: 0.0031 ± 0.0003, P = 0.01). The ratio of GLUT1 to NHE1 is significantly decreased in the blood of COVID‐19 patients who are subsequently intubated and/or die (severe disease) compared with patients with moderate disease (moderate disease: 0.497 ± 0.083 vs. severe disease: 0.294 ± 0.0336, P = 0.036). This ratio is even further decreased in the myocardium of patients who deceased from COVID‐19 in comparison with the myocardium of non‐infected donors. Conclusions: NHE1 and GLUT1 may be critically involved in the disease progression of SARS‐CoV‐2 infection. We show here that SARS‐CoV‐2 infection critically disturbs ion channel expression in the heart. A decreased ratio of GLUT1/NHE1 could potentially serve as a biomarker for disease severity in patients with COVID‐19.